Medical service in Spain : inter-departmental correspondence (copy) - Tewson, Vincent
042-0145-001 H.V. TEWSON. MR. J.S. MIDDLETON SECRETARY'S 7TH MAY, 1937. MEDICAL SERVICE IN SPAIN. If the enclosed lady only has a month's leave this would mean that she would only be in Spain about a fortnight, and I would suggest, that in view of the expense involved for her and the difficulty of making arrangements to dovetail services for so short a period, that it does appear to be impracticable. Would you care to mention to her that there may be some work in connection with the Basque children? HVT/EK/848. 292/946/42/145